Whats the square root of 40

Answers

Answer 1
Answer:

To simplify the square root of 40, first notice that 40 is not a perfect square. We can start by setting up a factor tree. 40 factors as 2 times 20. 20 factors as 2 times 10 and 10 factors as 2 times 5. There is a pair of two's so this means that a two can come out of the radical. The 2 and the 5 do not match up so they will stay inside the radical. If you multiply them together you will make 10.

Therefore, the square root of 40 simplifies to 2 root 10.

Image provided.

Answer 2
Answer:

The numerical expression √40 in the simplified form will be 2√10.

Given that:

Number, n = √40

Algebra is the study of algebraic expressions, while logic is the manipulation of those concepts.

It is a method for dividing a number into pieces that will be multiplied together.

The factors of the number 40 are calculated as,

40 = 2 x 2 x 2 x 5

40 = 2² x 10

The expression is simplified as,

√40 = √(2² x 10)

√40 = √(2)² x √10

The square root is canceled out by a square. Then the numerical expression is written as,
√40 = √(2)² x √10

√40 = 2 x √10

√40 = 2√10

More about the Algebra link is given below.

brainly.com/question/953809

#SPJ6


Related Questions

Find the product. a^4(3a ^2 - 2a + 1)
Cedric work 33.25 hours he makes 13.25 per hour what is his total straight pay for the past two weeks
10 + 10 =20the answer is 20
Radius of a circle with diameter 240mm
Write this equation in standard form 9x^2-4y^2-24y-72=0

3/4 (6x + 1) - 3x = 1/4 (2x - 1)

Answers

3/4 (6x + 1) - 3x = 1/4 (2x - 1) . The purpose of this question is to solve for x.

\mathbf{x = (-4)/(13)}

Given that:

  • 3/4 (6x + 1) - 3x = 1/4 (2x - 1)

When calculating algebraic expression, we take note of integers in bracket first, then we collect the like terms in order to find the value of x.

\mathbf{(3)/(4) (6x + 1) - 3x =(1)/(4) (2x - 1) }

Let's multiply both sides by 4 to eliminate the fraction.

\mathbf{((3)/(4) * 4) (6x + 1) - 3x =((1)/(4) * 4 ) (2x - 1) }

\mathbf{(3) (6x + 1) - 3x =(1 ) (2x - 1) }

  • Open brackets;

18x + 3  - 3x = 2x - 1  

  • By rearrangement;

18x - 3x + 3 = 2x - 1

15x + 3 = 2x - 1

  • Collect like terms

15x - 2x = - 3 - 1

13x = - 4

  • Divide both sides by 13

\mathbf{(13x)/(13) = (-4)/(13)}

\mathbf{x = (-4)/(13)}

Learn more about algebraic expressions here:

brainly.com/question/11227332?referrer=searchResults

3/4*(6x+1)-3*x-(1/4*(2*x-1))=0
X=1

Please help asap! file attached below!

Answers

I got B but you may want to check with some other people's answer choices before you put in my answer hope this helps in the meantime though I'm pretty confident in my answer

Find the solution to the system of 5x+2y=-24 x-y=5

Answers

So to do this, we have to get rid of one of the variables by adding or subtracting the two equations together.
I will get rid of y. So, we can multiply the second equation by 2. This gives us
2x-2y=10
Now, we can add both equations
This gives us 7x=-14
Therefore, x = -2
Plug that into another equation.
-10 + 2y=-24
Therefore, y = -7

Hope this helped!! :D
5x + 2y = -24 ⇒ 5x + 2y = -24
1x -  1y =    5 ⇒ 2x -  2y =  10
                                  7x = -14
                                   7       7
                                     x = -2
                                x - y = 5
                              -2 - y = 5
                            + 2       + 2
                                   -y = 7
                                   -1   -1
                                     y = -7
                               (x, y) = (-2, -7)

50 POINTS !!!!
HELP ME PLZZ I NEED HELP WITH THIS!!

Answers

твоја симпатијатвоја симпатијатвоја симпатијатвоја симпатијатвоја симпатијатвоја симпатија

Answer: 5.50

Step-by-step explanation:

1.50 + 1.00 = 2.50 . 8.00 - 2.50 = 5.50

Help please!! I will give crown! :D

Answers

Answer:

C. Please mark Brainliest!!!!!!

Step-by-step explanation:

You move it 5 over, so it is 3.844x10^5

Answer:

answer is c

bc you multiply 3.844 by 100000 to get 38440

Step-by-step explanation:

Brainly for correct answer!!The diagram shows two parallel lines cut by a transversal. One angle measure is shown.


Find the values of A B C D E F and G

Answers

The measure of the angles are a = 54, b = 54, c = 126, d = 54, e = 126, f = 54, and g = 126 degrees.

What are vertically opposite angles?

It is defined as the angles when two lines intersect each other and at the intersecting point, some pair of angles are formed which we call vertically opposite angles, as the name describes that they have vertically opposite angles.

It is given that:

The diagram shows two parallel lines cut by a transversal.

As we know from the definition of the vertically opposite angles:

b = 54 degrees

a + c = 54 + b  (a = c)

2a = 54x2

a = 54 degrees

Since a and g are opposite interior angles, they are congruent, so you proceed with the process as you did for the first and check to see if the angles are acute or obtuse to ensure that the angle measurements are accurate.

Similarly:

b = 54

c = 126

d = 54

e = 126

f = 54

g = 126

Thus, the measure of the angles are a = 54, b = 54, c = 126, d = 54, e = 126, f = 54, and g = 126 degrees.

Learn more about the vertically opposite angles here:

brainly.com/question/24287162

#SPJ2

Answer:

a= 126

b= 54

c= 126

d= 54

e= 126

f= 54

g= 126

Step-by-step explanation:

To find a you would subtract 54 from 180 which would give you 126

Since a and b are another linear pair they would also add up to 180.

Then you move to c which is a linear pair with 54 so it is 126.

Because a and g are alternate interior angles they are congruent and they you continue with the same process for the first and check by seeing if the angles would be obtuse or acute to see if the angle measures would be correct.